2010
DOI: 10.1016/j.cca.2009.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Increased MMA concentration and body mass index are associated with spontaneous abortion in Brazilian women

Abstract: Increased serum MMA and BMI concentrations are associated with spontaneous abortion in Brazilian women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
0
5
0
2
Order By: Relevance
“…That study found significantly higher plasma homocysteine levels just before delivery as assessed by an automated enzymatic assay in pregnant women with preeclampsia than in normotensive pregnant women [11]. Other studies have reported an association between MMA and homocysteine levels and maternal and neonatal outcomes [9,26,27]. Previous studies were performed with variable specimen types (serum or plasma) and determined the concentrations using GC-MS or LC-MS/MS, which makes direct comparison of their results difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That study found significantly higher plasma homocysteine levels just before delivery as assessed by an automated enzymatic assay in pregnant women with preeclampsia than in normotensive pregnant women [11]. Other studies have reported an association between MMA and homocysteine levels and maternal and neonatal outcomes [9,26,27]. Previous studies were performed with variable specimen types (serum or plasma) and determined the concentrations using GC-MS or LC-MS/MS, which makes direct comparison of their results difficult.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to the small number of adverse maternal and neonatal outcomes we observed, which may not have been great enough to provide statistical significance. However, although previous studies have reported that maternal vitamin B12 deficiency is associated with an increased risk of adverse pregnancy outcomes (e.g., neural tube defects, preterm delivery, and intrauterine growth retardation) [1], there have been inconsistent results among studies on MMA and homocysteine levels and maternal and neonatal outcomes [7,9,11,26,27]. Our results concerning homocysteine were comparable with those of a previous study performed in pregnant Korean women which reported no significant association between plasma homocysteine levels and pregnancy outcomes such as preterm delivery, GDM, SGA, placenta abruption or placenta previa, although there was an association between plasma homocysteine levels and preeclampsia [11].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that the causes of MA are multiple and complex, including abnormalities in chromosome number and structure (7,8), immune dysfunction (9,10), endocrine dysfunction (11), abnormal intrauterine environment (12), hereditary thrombophilia (13), systemic infectious diseases (14,15) and environmental factors (3). However, in ~50% of affected patients, the reason for the occurrence of MA and the associated pathogenesis remain elusive (16). By analyzing the decidua tissue of 11 SA cases and 9 cases of selective termination of pregnancy by immunohistochemistry and the terminal deoxynucleotidyl-transferase mediated dUTP nick end labeling (TUNEL) assay, it was revealed that the rate of positive staining for M30 in decidual tissue cells from the SA was 2.5-fold higher than that in the selective termination group, while the apoptotic index was up to 5-fold higher (17).…”
Section: Introductionmentioning
confidence: 99%
“…Após a doação de um grupo metil,a SAM se converte em Sadenosilhomocisteína (SAH) (Miller, 2008;Kalhan e Marczewski, 2012). Quando ocorre alteração da razão SAM/SAH, pode ocorrer alteração na metilação do DNA, com incorporação de uracila, desencadeando mutações, quebras cromossômicas e formação de micronúcleos (Govindaiah, Naushad et al, 2009;Benammar, Sermondade et al, 2012), podendo interferir no desenvolvimento fetal (Benammar, Sermondade et al, 2012 (Forges, Monnier-Barbarino et al, 2007); aumento da possibilidade de má formação congênita, descolamento prematuro da placenta, abortos espontâneos e pré-eclâmpsia (Forges, Monnier-Barbarino et al, 2007;Guerra-Shinohara, Pereira et al, 2010). Além disso, a tHcy pode ser tóxica ao embrião, pela geração de lesões oxidativas (Benammar, Sermondade et al, 2012), e pode aumentar o potencial trombogênico (Durand, Lussier-Cacan et al, 1997;Benammar, Sermondade et al, 2012).…”
Section: Homocisteínaunclassified
“…No presente estudo, as mulheres do AER primário portadoras do genótipo (Furness, Fenech et al, 2008;Guerra-Shinohara, Pereira et al, 2010).…”
Section: Alguns Estudos Mostraram Que Indivíduos Com O Haplótipounclassified